2016
DOI: 10.1080/09712119.2016.1174122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of esterified glucomannan on broilers exposed to natural mycotoxin-contaminated diets

Abstract: The purpose of this study was to evaluate the effect of esterified glucomannan (E-GM) on performance, immunity, blood haematological and serum biochemical parameters in broilers exposed to diets naturally contaminated with mycotoxins. A total of 630 one-day-old male broiler chicks (Ross 308) were randomly assigned to 9 treatments and 5 replicates of 14 chicks based on factorial (3 × 3) arrangement in completely randomized design. The dietary treatments included 3 levels of substituting naturally contaminated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(58 reference statements)
4
4
0
Order By: Relevance
“…The AF and/or OT intoxicated chicks in control positive groups 2, 5 and 8 showed significant (P<0.05) decrease in ND and IBD antibody titers when compared with the negative control group (Tables 11-14). The reduction in the antibody titers was in agreement with several previous reports of Ibrahim et al, (2000); Raju and Devegowda, (2002); Oguz et al,(2003); Verma et al, (2004); Ghahri et al, (2010);Abd El-Ghany et al, (2013); Bhatti et al,(2017) and Mohaghegh et al,(2017) who used dietary inclusion of AF in broiler chicken. Similarly, Raju and Devegowda, (2002); Santin et al,(2002); Verma et al, (2004); El Aroussi et al,( 2006) & ( 2008) ; Xue et al, (2010); Awaad et al, (2011); Indresh and Umakantha, (2013); Hanif and Muhammad, 2015;Bhatti et al,(2017) and Mohaghegh et al,(2017) recorded the same results in chicks fed OT contaminated diets.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The AF and/or OT intoxicated chicks in control positive groups 2, 5 and 8 showed significant (P<0.05) decrease in ND and IBD antibody titers when compared with the negative control group (Tables 11-14). The reduction in the antibody titers was in agreement with several previous reports of Ibrahim et al, (2000); Raju and Devegowda, (2002); Oguz et al,(2003); Verma et al, (2004); Ghahri et al, (2010);Abd El-Ghany et al, (2013); Bhatti et al,(2017) and Mohaghegh et al,(2017) who used dietary inclusion of AF in broiler chicken. Similarly, Raju and Devegowda, (2002); Santin et al,(2002); Verma et al, (2004); El Aroussi et al,( 2006) & ( 2008) ; Xue et al, (2010); Awaad et al, (2011); Indresh and Umakantha, (2013); Hanif and Muhammad, 2015;Bhatti et al,(2017) and Mohaghegh et al,(2017) recorded the same results in chicks fed OT contaminated diets.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction in the antibody titers was in agreement with several previous reports of Ibrahim et al, (2000); Raju and Devegowda, (2002); Oguz et al,(2003); Verma et al, (2004); Ghahri et al, (2010);Abd El-Ghany et al, (2013); Bhatti et al,(2017) and Mohaghegh et al,(2017) who used dietary inclusion of AF in broiler chicken. Similarly, Raju and Devegowda, (2002); Santin et al,(2002); Verma et al, (2004); El Aroussi et al,( 2006) & ( 2008) ; Xue et al, (2010); Awaad et al, (2011); Indresh and Umakantha, (2013); Hanif and Muhammad, 2015;Bhatti et al,(2017) and Mohaghegh et al,(2017) recorded the same results in chicks fed OT contaminated diets. The reported depression in ND and IBD antibody titer values in the present study is a clear indication for the immunosuppressive effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Exposure of broilers to diet contaminated with 6.5 mg/kg DON, 0.47 mg/kg 15-acetyl-DON and 0.73 mg/kg ZEN showed significantly reduced feed intake and lowered CD4+ and CD8+ cells at Days 3 and 14 compared to birds fed uncontaminated diet [22]. Similarly, a broiler diet containing up to 0.4 mg/kg AFB1, 0.2 mg/kg OTA and 0.3 mg/kg DON caused reduced feed intake and feed efficiency as well as antibody titre against Newcastle disease and infectious bursal diseases [23]. Filho et al [24] also observed a decrease in feed intake (35%) and body weight (50%) in broiler chicken exposed to 2 mg/kg AFB1 and 100 mg/kg FB1 [24].…”
Section: Introductionmentioning
confidence: 91%
“…The immunosuppressive effect of AFs was further clearly noticed by the lower macrophage phagocytic activity and TLC (Abdel-Wahhab et al 2002;Basmacioglu et al 2005;Celik et al 2000;Oguz et al 2000), particularly after challenge with H9N2. Lymphocytes and WBC were decreased and heterophils were increased without any noticeable influence on monocyte and eosinophil in male broiler chickens exposed to mycotoxins naturally contaminated diets (Mohaghegh et al 2016). The possibility of phagocytic depression during mycotoxicosis may be due to inhibition of DNA, RNA and protein synthesis in macrophages after mycotoxins exposure; or due to alterations in metabolic processes, principally glycolysis essential for phagocytosis (Qureshi and Hagler 1992).…”
Section: Discussionmentioning
confidence: 99%